DIGITAL CONSUMER LITERACY, FOMO, AND THE RISKS OF ONLINE LOANS FOR STUDENTS AT PP DARUL ARQOM PURWOREJO - DINDA SUKMANINGRUM; DODI SETIAWAN RIATMAJA; NARWANTO NURCAHYO; NAIMA ANDLEEB (SMARTINDO, 2026)
The development of digital technology and social media has transformed the consumption patterns of the younger generation, including santri who are now increasingly exposed to the digital ecosystem. This community empowerment program aims to improve digital consumer literacy, raise awareness of the Fear of Missing Out (FOMO) phenomenon, and enhance understanding of the risks of online loans among santri at PP Darul Arqom Muhammadiyah Jono Purworejo. Activities were conducted using an interactive educational approach based on the Stimulus-Organism-Response (S-O-R) framework, including interactive lectures, case simulations, group discussions, and digital campaigns. The results of the activities showed an increase in participants’ knowledge regarding the dangers of FOMO, their ability to identify illegal online lending practices, and their readiness to adopt responsible financial behaviors. This program contributes to shaping students who are digitally savvy and critical of consumerist pressures in the e-commerce era.